Methodology for engineering calculation of working bodies for shallow tillage - S. I. Kambulov; G. G. Parkhomenko; O. S. Babenko; S. V. Belousov (Сельскохозяйственные машины и технологии, 2023)
This study emphasizes the need for a comprehensive determination of parameters and operational modes of the working body, employing mutually agreed dependencies. (Research purpose) The research aims to develop a methodology for calculating parameters and operational modes for a novel shallow tillage working body, considering the required technological process indicators and soil properties. (Materials and methods) A force interaction diagram has been constructed, enabling the establishment of a relationship between working body parameters and soil physical and mechanical properties. This analysis yields a correlation between the working body parameters (crumbling angle) and unit operation mode (speed). (Results and discussion) The innovative aspect lies in utilizing the relationships linking the cultivator parameters and operational modes with the soil properties and process indicators. For shallow tillage, a working body with curved surfaces and increased streamlining is proposed. Various single-tier and multi-tier conﬁgurations, along with corresponding working body widths aligned with cultivator width, are presented. (Conclusions) The paper introduces an engineering calculation method, determining the following working tool parameters: the crumbling angle of 15 degrees, the length of 30 centimeters, the width of 45 centimeters, the opening angle of 75-110 degree, the elevation angle of 10 degrees at the depths of 6-16 centimeters, and the speed of up to 14 kilometers per hour. The technological process involves soil crumbling resulting in a characteristic clod size of up to 25 millimeters, and tractive resistance reaching up to 3.7 kilonewtons.